2011
DOI: 10.4331/wjbc.v2.i6.146
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide signaling axis in human leukemia

Abstract: The vasoactive intestinal peptide (VIP) signaling axis constitutes a master "communication coordinator" between cells of the nervous and immune systems. To date, VIP and its two main receptors expressed in T lymphocytes, vasoactive intestinal peptide receptor (VPAC)1 and VPAC2, mediate critical cellular functions regulating adaptive immunity, including arresting CD4 T cells in G1 of the cell cycle, protection from apoptosis and a potent chemotactic recruiter of T cells to the mucosa associated lymphoid compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 129 publications
0
18
1
Order By: Relevance
“…It functions through binding to its specific receptors VPAC 1 and VPAC 2 . Both receptors are expressed in lymphoid cells, specifically in CD4 T cells [19][20][21]. However, whereas VPAC 1 is constitutively expressed, VPAC 2 is induced after cell activation [22].…”
Section: Introductionmentioning
confidence: 99%
“…It functions through binding to its specific receptors VPAC 1 and VPAC 2 . Both receptors are expressed in lymphoid cells, specifically in CD4 T cells [19][20][21]. However, whereas VPAC 1 is constitutively expressed, VPAC 2 is induced after cell activation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The up-regulation of Ikaros here may indicate a decline in lymphocyte proliferation after treatment with VIP. Interestingly, Ikaros has been shown to up-regulate VIP receptor expression through the 12 putative binding sites in the promotor regions in each of the two VIP receptor genes (Dorsam, Benton, Failing, & Batra, 2011). Patients in the study showed an up-regulation in all 5 Ikaros isoforms (Ikz1; +1.24 fold, Ikz2; +1.41, Ikz3; +1.41, Ikz4; +1.38, and Ikz5; +1.18).…”
Section: Ikaros Transcription Factorsmentioning
confidence: 76%
“…In a previous study, VIP receptor antagonists facilitated chemotherapeutic agents to cause apoptosis in certain cancer cell lines (33); VIP is cell context-dependent and is known to contribute to leukemogenesis (34). There is reported similarity of VIP with pituitary adenylate cyclase, which belongs to the secretin family.…”
Section: Vasoactive Intestinal Peptide (Vip) and Pituitary Adenylate mentioning
confidence: 96%
“…VIP is produced by various cells, however, its primary location is within neurons; this peptide is expressed in the peripheral and central nervous systems, as well as in certain tumors (3,(33)(34)(35)(36). In a previous study, VIP receptor antagonists facilitated chemotherapeutic agents to cause apoptosis in certain cancer cell lines (33); VIP is cell context-dependent and is known to contribute to leukemogenesis (34).…”
Section: Vasoactive Intestinal Peptide (Vip) and Pituitary Adenylate mentioning
confidence: 99%